2015
DOI: 10.18805/lr.v38i6.6725
|View full text |Cite
|
Sign up to set email alerts
|

Yield and profitability of groundnut (Arachis hypogaea L.) as influenced by sowing dates and nutrient levels with different varieties

Abstract: A field study was conducted to evaluate the date of sowing of groundnut (<italic>Arachis hypogaea</italic> L.) during <italic>kharif</italic> 2009 and 2010. Experiment was laid out in split-plot design by assigned dates of sowing (20 April, 15 May, 9 June and 4 July) and varieties (‘HNG 10’ and ‘TG 37A’ ) in main plots and four fertility levels (without fertilizers, 20 N + 40 P<sub>2</sub>O<sub>5</sub>, 30 N + 60 P<sub>2</sub>O<sub>5</sub>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…Even after the flowering also try to accumulate as much as photosynthates into the sink thus delaying the days to maturity. The results are in line with findings of Thavaprakash (2000) and Meena, and Yadav, (2015).…”
Section: Resultssupporting
confidence: 91%
“…Even after the flowering also try to accumulate as much as photosynthates into the sink thus delaying the days to maturity. The results are in line with findings of Thavaprakash (2000) and Meena, and Yadav, (2015).…”
Section: Resultssupporting
confidence: 91%
“…Relative water content of fenugreek leaves was recorded periodically at different growth stages (seedling, branching, flowering, pod formation and pod development respectively) of fenugreek in different date of sowing. During seedling, branching stage the maximum relative water content was Yadav (2015) found significantly higher crop stand at harvest for the later sown crops among all sowing dates. (Fig.5).…”
Section: Resultsmentioning
confidence: 93%
“…Similarly improved variety enhanced the yield by 25.41% over farm saved seed. Meena and Yadav (2015) was also reported that the high yielding varieties helps in increasing the productivity of major field crops.Optimum nutrition 36.20% over farmers practices. Nawale et al(2009) who obtained that the optimum dose of fertilizers increased the yield of chickpea by 34.7% as compared to farmers practices.Weed management enhance the yield of chickpea by 41.24% over farmers practices, Pandit et al (2017) and Mishra (1997).…”
Section: Resultsmentioning
confidence: 96%
“…The varieties cultivated by the farmers which are low yielding and susceptible to pests and disease. The high yielding varieties helps increasing the productivity Yadav, 2015.). Hence, on farm trail were conducted on chickpea in Grid zone of M.P., to find out the effect of improved practices evolved by research over farmers practices.…”
Section: Introductionmentioning
confidence: 99%